Effect of rainfall on growth and yield of rice in Konkan coast (MAUSAM, 1993)
In this Study, relationship between rainfall and rice yield has been investigated in Ratnagiri and Thane districts of Maharashtra using 37 year's (1951.1987) data. Weekly water balance has been worked out in developing a yield index and its association with yield examined. Planting rates have been calculated assuming two categories of empirical rainfall accumulations of 450 and 500 mm. The yields were correlated with rainfall during selected growth phases, total rainfall, the yield index and the technological trend. Effects of late or early onset on yield has also been examined. It appears that 450 mm rainfall accumulation from Ist June gives a ~reasonably accurate indication of transplanting paddy in Konkan. Technology seems.. to have much influence on the paddy yield. Results also reveal that rainfall during early growth phases is significantly related to the yield the date of planting was not found to/have a determining influence on the yield.